Yargıtay'ın Kat Karşılığı İnşaat Sözleşmelerine İlişkin Bazı İçtihatlarının Eleştirisi - Öz, Turgut (Seçkin Yayıncılık, 2018)
Kat karşılığı inşaat sözleşmleri hakkındaki Yargıtay içtihatlarında bazı kanuna uymayan çıkarlar dengesini iyi kuramayan ve çelişkili içtihatlar olduğu kanısındayım. Özellikle şu üç hususa ilişkin kararlar bu çerçevede zikredilebilir. İlki, kanunda aranmamasına rağmen bu sözleşmeden dönmenin mutlaka mahkemeye başvurularak yapılması gerektiği içtihadıdır. İkincisi, vaktiyle yükleniciden taşınmaz mülkiyeti devralan üçüncü kişiler iş arsa sahibinin sözleşmeden dönmesi üzerine bu haklarını daima kaybedecekleri içtihadıdır. Üçüncüsü ise sözleşmeden dönme üzerine o zamana kadar yapılan işler için yükleniciye sebepsiz zenginleşme hükümlerine göre ödenmesi gereken tutar hakkında farklı ve çelişkili hesaplama yöntemlerini Kabul eden içtihatlardır.

I am in the opinion that there are some case laws of Court of Cassation which some are contrary to law; some are not conducive to establish a balance interests and some are contradictory. In particular the following three of them can be cited: Firstly, decisions about the necessity of filing a lawsuit for termination of contract. Secondly, decision about the certainly losing the rights of third persons who had them from the contractor in case the work land owner rescind the contract, Third decisions which contain different and conflicting calculation methods about the amount that must be paid to the contractor for the works which have already been made by him according to the rules of unjust enrichment upon the termination of contract.
A Critical Essay on Some Case Laws of Court of Cassation About Flat for Land Basis Construction Contracts
Keywords: Kat karşılığı inşaat; Fesih davası; Sözleşmeden dönme; Sebepsiz zenginleşme; Sebebe bağlılık; Soyutluk; Flat for Land Basis; Lawsuit for Termination; Rescind the Contract; Unjust Enrichment; Causal Transaction; Abstract Transaction